Application of a methodology in health regulation to optimize quality management (Research, Society and Development, 2022)
Introduction: This article aims to disclose a methodology applied in health regulation to optimize quality management. The proposed theme will allow the analyst to better understand how to manage with a focus on the client, in health regulation. Method: This is a methodological research, in which existing knowledge was used in a systematic way for the elaboration of a new intervention or improvement of an existing intervention. In it, the researcher aims to develop a reliable, accurate and usable instrument that can be used by other researchers. This proposed methodology is divided into three stages. 27 professionals in the area of ​​regulation were interviewed, with 99% of the interviews being used. After explaining what the study was about, it was identified whether the client was aware of what/who or what the sector was for; if not, a brief explanation was given so that he felt able to respond. 16 customers participated. Results: Additionally, a Guide for the Implementation of Methodology for Quality Management in Health Regulation was created. Conclusion: The proposed methodology presents a framework and structuring elements, which provide a broader understanding of the existing relationships between the institution, professionals and clients, based on their needs. and perceptions about Health Regulation.